THE ROLE OF GROWTH AND ENDOTHELIAL FACTORS IN HEMOSTATIC DISORDER IN CHILDREN WITH THE SYNDROM DELAYED FETAL - S. B. Berezhanskaya; E. A. Lukyanova; A. S. Todorova; E. Y. Kaushanskaya (Медицинский вестник Юга России, 2013)
Violation of the natural defense mechanisms of endothelial dysfunction and an imbalance can occur many neurohumoral factors. The imbalance of angiogenic and antiangiogenic growth factors, endothelial, platelet factor closely related to disorders of hemostasis, promotes the development of generalized endothelial dysfunction and is the basis of placental insufficiency, and is central to fetal growth and neonatal characteristics of the child’s development. The mechanisms regulating these processes in normal and pathological conditions play an important role of thromboxane and prostacyclin, which are derivatives of polyunsaturated fatty acids. Which indicates the feasibility of studying the role of vascular endothelial growth factor and hemostasis disorders in children with fetal growth retardation syndrome.